Novel modified blumgart anastomosis reduces clinically relevant pancreatic fistula after pancreaticoduodenectomy: a retrospective study using inverse probability of treatment weighting - Ye, Lin; Jian, Zhiyuan; Yue, Wanrong; Weng, Jun; Mo, Qingrong; Li, Gaoshi; Li, Renjian; Shi, Hao; Zhou, Haozhe; Yu, Yaqun (Frontiers in Surgery, 2025)
BackgroundClinically relevant postoperative pancreatic fistula (CR-POPF) remains a significant complication after pancreaticoduodenectomy (PD). We implemented a novel modified Blumgart pancreaticojejunostomy (m-BPJ) technique with anchoring approach and omental reinforcement, and evaluated its efficacy compared to conventional pancreaticojejunostomy (c-PJ).MethodsThis retrospective study included patients who underwent PD from January 2020 to December 2024. Patients were divided into m-BPJ (n = 85) and c-PJ (n = 130) groups. Inverse probability of treatment weighting (IPTW) was applied to balance baseline characteristics. The primary endpoint was CR-POPF incidence. Secondary endpoints included operative parameters, postoperative recovery indicators, and complications.ResultsAfter IPTW, CR-POPF incidence was significantly lower in the m-BPJ group (6.4% vs. 15.6%, p = 0.031). The m-BPJ group showed shorter PJ anastomosis time (21.1 ± 5.5 vs. 29.0 ± 7.4 min, p < 0.001), operation time (287.5 ± 45.3 vs. 304.2 ± 53.6 min, p = 0.023), and less intraoperative blood loss (325 vs. 375 mL, p = 0.041). Postoperative recovery was accelerated, with faster gastrointestinal function recovery (3.2 ± 1.1 vs. 4.0 ± 1.4 days, p < 0.001), earlier oral intake (4.6 ± 1.3 vs. 5.7 ± 1.8 days, p < 0.001), and reduced hospital stay (12 vs. 14 days, p = 0.009). Multivariate analysis confirmed m-BPJ as an independent protective factor against CR-POPF (OR 0.34, 95% CI 0.13-0.82, p = 0.018), while BMI ≥25 kg/m² (OR 2.23, 95% CI 1.07–4.65, p = 0.033), soft pancreatic texture (OR 3.25, 95% CI 1.47–7.12, p = 0.003), and pancreatic duct diameter <3 mm (OR 2.35, 95% CI 1.12–4.97, p = 0.024) were independent risk factors. Subgroup analysis revealed greatest benefit in high-risk patients.ConclusionsOur m-BPJ technique with anchoring approach and omental reinforcement significantly reduces CR-POPF after PD, particularly in high-risk patients. This technique demonstrates improved surgical efficiency and postoperative recovery, providing a valuable option for safer pancreatic reconstruction following PD.